EFFECT OF SEROPOSITIVITY ON BONE MINERAL DENSITY IN CHRONIC INFLAMMATORY DISEASES - Nurgul Arıncı Incel,; Meryem Saraçoğlu,; Aynur Karagöz,; H. Rana Erdem, (Archives of Rheumatology, 2005)
Localised and generalised bone loss in chronic inflammatory diseases result in an increased risk of fractures with associated morbidity and mortality. Our aim was to observe bone mineral density (BMD) changes in seropositive and seronegative chronic inflammatory diseases and to evaluate the effect of clinical characteristics on BMD. 75 seropositive, 15 seronegative RA and 27 AS patients with 25 healthy volunteers were included in the study. Seronegative RA patients and all AS patients were accepted as the seronegative group. BMD measurements were carried out at lumbar spine and femur neck by DEXA. We found significant difference between T scores of seropositive patients and control groups. The difference was not statistically significant between seronegative and seropositive groups though BMD values were lower for the seropositive group at either site. For the seronegative group, we found no statistically significant difference between spondyloarthropathy and seronegative RA patient groups in terms of spinal and femoral T scores. We suggest that the increased risk of OP in chronic inflammatory diseases is present but not dependent on the seropositive and seronegative characteristic of the disease.